A new species of the genus Acarophenax (Acari: Heterostigmata: Acarophenacidae) associated with Sphindus sp. (Coleoptera: Sphindidae) from Iran - Vahid Rahiminejad; Hamidreza Hajiqanbar (Persian Journal of Acarology)
The mite Acarophenax sphindi Rahiminejad & Hajiqanbar sp. nov. (Acari: Heterostigmata) collected under head of the host beetle, Sphindus sp. (Coleoptera: Sphindidae) is described and illustrated from Oak forests of Golestan province, northern Iran. It is first record of the beetle family Sphindidae (Col.: Cucujoidea) as an acarophenacid host. Moreover, host range of the genus is reviewed and a key to world species of the genus Acarophenax Newstead & Duvall, 1918, is provided.